2010
DOI: 10.1111/j.1528-1167.2010.02626.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the cannabinoid‐receptor antagonist, SR141716, on the early stage of kainate‐induced epileptogenesis in the adult rat

Abstract: SummaryPre-treatment with the endocannabinoid-receptor antagonist, SR141716, has been reported to suppress the long-lasting hyperexcitability and increased seizure susceptibility present after 30 min of hyperthermia-induced convulsions in immature rats, an animal model of complex febrile seizures in children, which may be a cause of temporal lobe epilepsy. The present experiments tested the hypothesis that SR141716 suppresses epileptogenesis in the adult kainate model, an animal model of temporal lobe epilepsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
2
14
2
1
Order By: Relevance
“…In apparent contrast, van Rijn et al (2011) reported that the CB1R antagonist rimonabant can exert a pro-epileptogenic effect after chronic administration in naïve rats (van Rijn et al, 2011). Another study in the kainate model of temporal lobe epilepsy did not report relevant effects of rimonabant on epileptogenesis (Dudek et al, 2010). Considering these controversial findings, it is obviously necessary to further explore the role of CB1Rs in epileptogenesis in more detail.…”
Section: Seizures Increase Cb1r Density In the Pyramidal Cell Layer Omentioning
confidence: 97%
See 1 more Smart Citation
“…In apparent contrast, van Rijn et al (2011) reported that the CB1R antagonist rimonabant can exert a pro-epileptogenic effect after chronic administration in naïve rats (van Rijn et al, 2011). Another study in the kainate model of temporal lobe epilepsy did not report relevant effects of rimonabant on epileptogenesis (Dudek et al, 2010). Considering these controversial findings, it is obviously necessary to further explore the role of CB1Rs in epileptogenesis in more detail.…”
Section: Seizures Increase Cb1r Density In the Pyramidal Cell Layer Omentioning
confidence: 97%
“…The detailed etiology of epileptogenesis remains unknown, and whether the endocannabinoid system is involved in epileptogenesis and promotes anti-or proconvulsant effects is still controversially discussed (Dudek et al, 2010;Echegoyen et al, 2009). This might be partly related to the dichotomous role of endocannabinoid signaling in different neuronal subpopulations.…”
Section: Introductionmentioning
confidence: 98%
“…21 Animal models of neonatal brain injury also support an association between neonatal seizures and epilepsy. [22][23][24] Whether seizures in the setting of an acute perinatal stroke have a deleterious effect on developing brain or are simply a marker for greater underlying brain injury is unknown, but the association with childhood epilepsy is worrisome. An active seizure focus in the setting of acute stroke could increase metabolic demand in ischemic penumbra and worsen brain injury, or the presence of neonatal seizures may contribute to epileptogenesis during a crucial developmental window.…”
mentioning
confidence: 99%
“…Andererseits konn te z. B. für den Endocannabinoidrezep torantagonisten Rimonabant dargestellt werden, dass lediglich eine sehr frühe Applikation 2 min nach einem experi mentell induzierten SchädelHirnTrau ma mit einem antiepileptogenen Effekt verbunden war, während die Applikation nach 20 min keinen entsprechenden Ef fekt ausübte [6].…”
Section: Zeitfenster Für Die Interventionunclassified